2015
DOI: 10.1111/phor.12122
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Parametric BIM Objects from Point Clouds Using Nurbs

Abstract: This paper presents an innovative procedure to create parametric building information modelling (BIM) objects from point clouds of complex architectural features. BIM technology requires an advanced parametric representation of the geometry involving spatial relationships, constraints and material properties. The aim of the procedure is a BIM-based reconstruction methodology that preserves the level of detail encapsulated in photogrammetric and laser-scanning point clouds, and relies on non-uniform rational ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 43 publications
2
64
0
1
Order By: Relevance
“…In addition, HBIM approach needs to face theoretical and pratical challenges and to fill gap regard the BIM: a wide discussion about differences between a) semantic object or unsegmented geometries, b) standardization or irregularity c) parametric intelligence or geometric accuracy is provided in (Apollonio et al, 2016). In HBIM field, the modelling phase and the semantic sub-division in various elements are sufficiently robust, although time-consuming (Garagnani and Manferdini, 2013) (Barazzetti et al, 2015) and based on proprietary tools . According several studies, the observed trend in the definition of HBIM is the creation of a model starting from survey data (i.e.…”
Section: State Of Artmentioning
confidence: 99%
“…In addition, HBIM approach needs to face theoretical and pratical challenges and to fill gap regard the BIM: a wide discussion about differences between a) semantic object or unsegmented geometries, b) standardization or irregularity c) parametric intelligence or geometric accuracy is provided in (Apollonio et al, 2016). In HBIM field, the modelling phase and the semantic sub-division in various elements are sufficiently robust, although time-consuming (Garagnani and Manferdini, 2013) (Barazzetti et al, 2015) and based on proprietary tools . According several studies, the observed trend in the definition of HBIM is the creation of a model starting from survey data (i.e.…”
Section: State Of Artmentioning
confidence: 99%
“…It also includes new bridges often characterized by variable curvature and cross sections. From this point of view, the lack of powerful BIM instruments able to reconstruct complex shapes is still a major drawback in BIM projects, and the generation of accurate historic BIM (Murphy et al, 2013) surveyed from laser scanning point clouds is a challenging task which requires the development of new libraries or the implementation of new algorithms (some examples are discussed in Fai et al, 2011;Baik et al, 2015;Oreni et al, 2014;Dore et al, 2015;Quattrini et al, 2015, Barazzetti et al, 2015c. In addition, the use of software for "pure" (direct) 3D modelling was not possible (e.g.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Considering the general purpose of the work, the modeling process targeted a hypothetical LOD level of 200 (compared now to LOD B in the new Italian regulations, named UNI 11337) and then turned to grasp especially masonry systems (with the relative openings) and structural systems with their tracking irregularities (Barazzetti at al., 2015a). The employed modeling strategy mainly exploited the traditional approach for creating 3D solid primitives by means of NURBS (Non Uniform Rational BasisSplines) and LOW-POLY meshes (Tang et al, 2010;Barazzetti at al., 2015b). Then, all the created primitives were translated in simple solid meshes.…”
Section: The Bim Modelingmentioning
confidence: 99%